Rapamycin Protects Skin Fibroblasts from Ultraviolet B-Induced Photoaging by Suppressing the Production of Reactive Oxygen Species - Dengke Qin (Cellular Physiology and Biochemistry, 2018)
Background/Aims: Ultraviolet B (UVB) irradiation alters multiple molecular pathways in the skin, thereby inducing skin photoaging. Murine dermal fibroblasts (MDFs) were subjected to a series of 4 sub-cytotoxic UVB doses (120 mJ/cm2), resulting in changes in cell shape, DNA damage, cell cycle arrest, extracellular matrix variations, reactive oxygen species (ROS) generation, and alterations in major intracellular antioxidant and cellular autophagy levels. Rapamycin (RAPA) is a new macrolide immunosuppressive agent that is primarily used in oncology, cardiology, and transplantation medicine and has been found to extend the lifespan of genetically heterogeneous mice. Several studies have shown that RAPA may have anti-aging effects in cells and organisms. Thus, in this study, we explored the effects and mechanisms of RAPA against the photoaging process using a well-established cellular photoaging model. Methods: We developed a stress-induced premature senescence (SIPS) model through repeated exposure of MDFs to ultraviolet B (UVB) irradiation. The cells were cultured in the absence or presence of RAPA for 48 h. Senescent phenotypes were assessed by examining cell viability, cell morphology, senescence-associated β-galactosidase (SA-β-gal) expression, cell cycle progression, intracellular ROS production, matrix metalloproteinase (MMP) synthesis and degradation, extracellular matrix (ECM) component protein expression, alterations in major intracellular antioxidant levels, and the cellular autophagy level. Results: Compared with the UVB group, pretreatment with RAPA (5 µM) significantly decreased the staining intensity and percentage of SA-β-gal-positive cells and preserved the elongated cell shape. Moreover, cells pretreated with RAPA showed inhibition of the reduction in the type I collagen content by blocking the UVB-induced upregulation of MMP expression. RAPA also decreased photoaging cell cycle arrest and downregulated p53 and p21 expression. RAPA application significantly attenuated irradiation-induced ROS release by modulating intracellular antioxidants and increasing the autophagy level. Conclusions: Our study demonstrated that RAPA elicited oxidative damage in vitro by reducing ROS accumulation in photoaged fibroblasts. The anti-aging effect can be attributed to the maintenance of normal antioxidant and cellular autophagy levels. However, determination of the definitive mechanism requires further study.